The role played by knowledge intensive business services in knowledge economy: New faces and challenges - Jo\~ao J. Ferreira; Cristina I. Fernandes (The International Journal of Management Science and Information Technology (IJMSIT), 2011)
Knowledge is now perceived as the basic core of organizations, is becoming more a role in the recognition and capitalization of entrepreneurial opportunities. A growing number of researches have been show knowledge as basis for creation of new organizations. This study aims to evidence the role played by knowledge intensive businesses services (KIBS) today and to highlight their new faces and challenges for 21st century. More specifically, it highlights how several critical factors are involved in development of competitive and innovative system. We argue that the contribution of these organizations on economic development is not a simple process, and to recognize the specific characteristics of KIBS and linking them within a specific context will be an important step.
Keywords: 650; Knowledge organizations; intensive knowledge; KIBS; service sector; Innovation